Literature Review: Innovations in Business Learning to Enhance Competencies and Insights of Vocational Students - Isnaini, Arif; Faizin, Moh; Murwani, F. Danardana; Wati, Andy Prasetyo (PT. EQUATOR SINAR AKADEMIA, 2024)
This research focuses on improving the competencies and insights of students in business learning at Vocational High Schools (SMK). Lack of innovation in teaching methods often results in a disinterest and lack of understanding of business materials. The study aims to explore and implement innovative approaches, such as technology integration and project-based learning, to enhance students' learning experiences. The use of technology, project-based learning, and collaboration with local business practitioners have shown positive results in increasing students' interest and understanding of business materials. The study emphasizes the importance of adopting innovative teaching methods to improve the relevance and effectiveness of business education in Vocational high schools.